Calcification intensity in planktonic Foraminifera reflects ambient conditions irrespective of environmental stress - M. F. G. Weinkauf; T. Moller; M. C. Koch; M. Kučera (Biogeosciences, 2013)
Planktonic Foraminifera are important marine calcifiers, and the ongoing change in the oceanic carbon system makes it essential to understand the influence of environmental factors on the biomineralization of their shells. The amount of calcite deposited by planktonic Foraminifera during calcification has been hypothesized to reflect a range of environmental factors. However, it has never been assessed whether their calcification only passively responds to the conditions of the ambient seawater or whether it reflects changes in resource allocation due to physiological stress. To disentangle these two end-member scenarios, an experiment is required where the two processes are separated. A natural analogue to such an experiment occurred during the deposition of the Mediterranean sapropels, where large changes in surface water composition and stratification at the onset of the sapropel deposition were decoupled from local extinctions of planktonic Foraminifera species. We took advantage of this natural experiment and investigated the reaction of calcification intensity, expressed as mean area density (MAD), of four species of planktonic Foraminifera to changing conditions during the onset of Sapropel S5 (126–121 ka) in a sediment core from the Levantine Basin. We observed a significant relationship between MAD and surface water properties, as reflected by stable isotopes in the calcite of Foraminifera shells, but we failed to observe any reaction of calcification intensity on ecological stress during times of decreasing abundance culminating in local extinction. The reaction of calcification intensity to surface water perturbation at the onset of the sapropel was observed only in surface-dwelling species, but all species calcified more strongly prior to the sapropel deposition and less strongly within the sapropel than at similar conditions during the present-day. These results indicate that the high-salinity environment of the glacial Mediterranean Sea prior to sapropel deposition induced a~more intense calcification, whereas the freshwater injection to the surface waters associated with sapropel deposition inhibited calcification. The results are robust to changes in carbonate preservation and collectively imply that changes in normalized shell weight in planktonic Foraminifera should reflect mainly abiotic forcing.